Danielo Joneso kardinalinių balsių spektrinės charakteristikos - Jaroslavienė, Jurgita; Kaukėnienė, Lidija (Kalbotyra, 2004)
The article gives a new acoustic analysis and the articulatory interpretation of Daniel Jones’ Cardinal Vowels. The results of the investigation in some respects are strikingly different from those presented, e.g., in Jassem’s book “Podstawy fonetyki akustycznej” (‘Principles of Acoustic Phonetics’, 1973).